Processing and high strain rate superplasticity of P/M 6061 Al alloy and 6061 Al/SiCp composites - Li, Xijiang. (2008)
The objective of this work is to achieve HSRS in P/M (Powder metallurgy) 6061 Al and composites and to study their deformation characteristics and mechanism of high strain rate superplasticity.